2017
DOI: 10.1371/journal.pone.0175027
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of modified surface microhardness measurement, focus variation 3D microscopy and contact stylus profilometry to assess enamel surface loss after erosive–abrasive challenges

Abstract: The aim of the study was to compare surface loss values after erosion—abrasion cycles obtained with modified surface microhardness measurement (mSMH), focus variation 3D microscopy (FVM) and contact stylus profilometry (CSP). We cut human molars into buccal and lingual halves, embedded them in resin and ground 200 μm of enamel away. The resulting surfaces were polished. To maintain a reference area, we applied Block-Out resin to partly cover the enamel surface. The samples were incubated in artificial saliva (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…Another common method used to measure surface loss is the profilometer 5 , 25 , 26 . However, a recent study showed that, although the different methods usually present different numerical values of surface loss measurements, both the indentation method and the profilometry have shown good correlation and either can be used in surface loss studies 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Another common method used to measure surface loss is the profilometer 5 , 25 , 26 . However, a recent study showed that, although the different methods usually present different numerical values of surface loss measurements, both the indentation method and the profilometry have shown good correlation and either can be used in surface loss studies 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Reproducibility of repeated measurements was also very high with low variations in the range of 0 ± 0.031 μm [Attin et al, 2009]. For the indentation analysis, an accuracy value of 0.18 µm and precision values of 0.01 and 0.08 µm have been reported for repeated measurements (10 measurements) [Gyurkovics et al, 2017]. The procedures of both profilometry as well as indentation analysis as performed in this study were mutually validated by experienced investigators from both university centers involved in order to minimize any methodological bias.…”
Section: Discussionmentioning
confidence: 81%
“…Mean enamel loss per tooth from toothbrush abrasion was 0.20 μm (range 0.01–0.31 μm measured from the difference in indentation depths at baseline 1.83 μm (0.07 μm) and after abrasion 1.66 μm (0.06 μm), as described in [20].…”
Section: Resultsmentioning
confidence: 99%
“…4). Studies have reported that the loss of dental hard tissue during the initial stage of erosion ranges from a few nanometers to a few micrometers [20, 23, 24]. When the erosion process reaches advanced stages where the enamel crystals dissolve and surface loss occurs, the reflection measurements (SRI) are less sensitive [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation